Platelet-derived calpain cleaves the endothelial protease-activated receptor 1 to induce vascular inflammation in diabetes - Kyselova, Anastasia (Basic Res Cardiol, 2020)
Diabetes mellitus is a major risk factor for cardiovascular disease. Platelets from diabetic patients are hyperreactive and release microparticles that carry activated cysteine proteases or calpains. Whether platelet-derived calpains contribute to the development of vascular complications in diabetes is unknown. Here we report that platelet-derived calpain1 (CAPN1) cleaves the protease-activated receptor 1 (PAR-1) on the surface of endothelial cells, which then initiates a signaling cascade that includes the activation of the tumor necrosis factor (TNF)-α converting enzyme (TACE). The latter elicits the shedding of the endothelial protein C receptor and the generation of TNF-α, which in turn, induces intracellular adhesion molecule (ICAM)-1 expression to promote monocyte adhesion. All of the effects of CAPN1 were mimicked by platelet-derived microparticles from diabetic patients or from wild-type mice but not from CAPN1(−/−) mice, and were not observed in PAR-1-deficient endothelial cells. Importantly, aortae from diabetic mice expressed less PAR-1 but more ICAM-1 than non-diabetic mice, effects that were prevented by treating diabetic mice with a calpain inhibitor as well as by the platelet specific deletion of CAPN1. Thus, platelet-derived CAPN1 contributes to the initiation of the sterile vascular inflammation associated with diabetes via the cleavage of PAR-1 and the release of TNF-α from the endothelial cell surface. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00395-020-00833-9) contains supplementary material, which is available to authorized users.